Gaya Kepemimpinan Perusahaan CV. Samaco Di Sidoarjo - Januar Pratama; Sofyan Lazuardi (CV ODIS, 2022)
The character of a leader is very influential in the creation of a good idea for the sake of mutual integrity in deciding a policy, a firm leader in terms of the good of the company is very necessary. Not only silent in an effort to deal with the company, there will be a death of the company caused by internal factors of the company. Employee performance is an achievement possessed by an employee to produce the desired quality and quantity to obtain responsibility in terms of career paths, of course the leader will assess before advancing to a position which will be assessed first to what extent the performance of each individual is not the same and can be used as a benchmark. leadership reference is appropriate or not. Each company also changes positions with the aim of being fresher in handling each job is when changing positions.